Natural gas to improve energy security in Small Island Developing States: A techno-economic analysis. (2017) - Raghoo, Pravesh; Surroop, Dinesh; Wolf, Franziska
Abstract: There is a paucity of studies on natural gas-based energy production in Small Island Developing States (SIDS) even though technological improvements today are likely to make the application of natural gas more and more feasible. The development of natural gas in some of the regions of the Pacific, Africa, Indian Ocean and Caribbean attracts nearby countries and the coming up of the compressed natural gas (CNG) technology which can serve regional markets are two motivations for SIDS to develop natural gas-based energy provision. A third factor concerns long-term energy security. Due to continued reliance on fossil fuels and slow uptake of renewable energy, there is a need to diversify SIDS' energy mix for a sustainable electricity industry. Comparing the opportunities and constraints of liquefied natural gas (LNG) and compressed natural gas (CNG) in a SIDS-specific context, this paper discusses how to improve the integration of natural gas in prevailing energy regimes in SIDS as an alternative fuel to oil and complementary to renewable energy sources. To illustrate feasibility in practice, a techno-economic analysis is carried out using the island of Mauritius as an example.